Co-construcción de soluciones barriales participativas, caso de estudio: “Barrio Santa Inés” parroquia Sucre, del cantón y provincia de Loja, periodo abril – septiembre 2022 - Japón Gutiérrez, Mayra Elizabeth (2023)
The realization of this project was focused on contributing to the Santa Inés neighborhood of the Loja canton in the construction of effective solutions, applying participatory, independent and democratic processes, aimed at meeting citizen demands and local reality; promoting neighborhood organization and participation; assisting with the neighborhood in the elaboration of the collective diagnoses of the problem; and supporting the design of solutions to the problems identified by the community. In order to meet the aforementioned objectives, an action research methodology was used, with a mixed approach, allowing to obtain important results through the information collection tools implemented such as observation sheets, surveys of the residents, interviews applied to the representative actors within the neighborhood, and participatory workshops. This has allowed, in the first instance, an approach to be generated with the board of directors and the residents of the neighborhood so that they know about the project of Co-construction of participatory neighborhood solutions, and are committed to participating in it; as well as the functions that neighborhood leaders must fulfill for the benefit of the neighborhood. Subsequently, with the application of the research techniques, it was possible to identify the three main problems that affect the residents (the lack of a physical place for meetings with the residents and the board of directors in the neighborhood; the difficulty of the residents to mobilize on buses urban areas; and finally, environmental pollution generated by smoke and bad odors, neighborhood garbage, and contamination from streams), which were validated by part of the population. After this, a neighborhood action plan was carried out in order to generate proposals to solve the aforementioned problems, generating activities with their respective managers and schedules so that it can be executed, and this plan was delivered to the neighborhood president so that, as leader together with the support of the residents, execute it and the three main demands that afflict the residents of the "Santa Inés" neighborhood can be resolved.